2020
DOI: 10.1002/fsn3.1527
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Quinoa flour and enzymes on the quality of gluten‐free bread

Abstract: Gluten‐free products usually are produced by refined flours such as rice and corn flour, which the bran is separated during processing. These flours are not nutritionally as rich as gluten containing products. Moreover, gluten‐free bread has several technical problems such as unfavorable texture, low volume, quick staling, and weaker color and taste compared with the wheat flour products. In this research, gluten‐free bread with various substitution of quinoa (0%, 15%, and 25%) was produced and the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Regarding firmness, the control bread showed the lowest value (22.3 N), while QF bread showed the highest one (59.86 N) (Table 5). Saadat et al (2020) reported that the replacement of GF flours with quinoa flour affected the hardness of the resulting breads, making the bread harder as the percentage of quinoa flour used increased [33]. Similar results were observed when 30% quinoa flour was used in the formulation of rice-based muffins, which showed firmness values almost twice as high as the control muffins made without the quinoa replacement [23].…”
Section: Crumb Analysismentioning
confidence: 81%
“…Regarding firmness, the control bread showed the lowest value (22.3 N), while QF bread showed the highest one (59.86 N) (Table 5). Saadat et al (2020) reported that the replacement of GF flours with quinoa flour affected the hardness of the resulting breads, making the bread harder as the percentage of quinoa flour used increased [33]. Similar results were observed when 30% quinoa flour was used in the formulation of rice-based muffins, which showed firmness values almost twice as high as the control muffins made without the quinoa replacement [23].…”
Section: Crumb Analysismentioning
confidence: 81%
“…Bread made from white rice flour benefitted from treatment with the protease thermoase, for example, displaying higher loaf volume and softer crumb; yet several other proteases, including Neutrase, did not produce the same effect, which the authors attributed to differences in raw materials (i.e., white vs. brown rice) (Kawamura-Konishi et al, 2013). Azizi et al (2020) found that protease improved quinoa bread volume and reduced bread staling, and attributed their results to modification of protein-starch interactions, which was caused by proteolytic activity.…”
Section: Proteasesmentioning
confidence: 99%
“…Using the same equipment for extension tests, the texture profile analysis (TPA) parameters have been calculated to grade the quality of the final product, as in the case of bread prepared by Azizi et al, Turkut et al, and Villanueva et al [ 54 , 66 , 69 ]. In a TPA analysis, hardness represents the necessary force to deform a material, springiness is the rate at which it returns to an undeformed state, cohesiveness is the strength of the internal bonds, and chewiness is the energy required to masticate the sample [ 119 ].…”
Section: Methodologies For the Measurements Of The Gluten Substitumentioning
confidence: 99%
“…In a TPA analysis, hardness represents the necessary force to deform a material, springiness is the rate at which it returns to an undeformed state, cohesiveness is the strength of the internal bonds, and chewiness is the energy required to masticate the sample [ 119 ]. In breadmaking, the effectiveness of an addition or modification must show an increase in values for springiness and cohesiveness to indicate that the product has higher stability and freshness after the treatment [ 66 ]. However, like peak force, hardness and chewiness must show intermediate values, or else the bread would be too hard or too soft for consumption.…”
Section: Methodologies For the Measurements Of The Gluten Substitumentioning
confidence: 99%
See 1 more Smart Citation